PECULIARITIES OF 24 HOUR AMBULATORY BLOOD PRESSURE MONITORING INDICES IN HYPERTENSIVE PATIENTS OF DIFFERENT AGE GROUPS - V.S. Pasko (Медична наука України, 2022)
Relevance. Until now, there is an ongoing debate about the value of different indicators of blood pressure (BP) − systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse blood pressure (PBP) as predictors of essential hypertension (EH). In this regard the issue of target BP levels in patients of different ages remains studied incompletely.